Iraqi women’s participation in the popular movement, a field study - Assistant. Prof. Dr. Asmaa Jamil Rasheed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Iraqi women’s participation in the popular movement, a field study